THE DYNAMICS OF FATHERS' ROLES IN MODERN FAMILIES: A FAMILY LAW AND FAMILY PSYCHOLOGY PERSPECTIVE - Nasywa Nabilah Nugroho; Irwansyah Irwansyah; Dhiauddin Tanjung (Journal Analytica Islamica, 2026)
This study examines the integration of the father's role in modern families from both legal and psychological perspectives. In the evolving dynamics of contemporary society, the father's role is no longer limited to being the breadwinner but also extends to that of an educator, moral guide, and emotional stabilizer within the family. Using a descriptive-analytical method with a literature-based approach, this research explores how paternal involvement influences character formation, emotional stability, and the social development of children. The findings indicate that, legally, fathers share equal responsibility with mothers in parenting, as stipulated in the Marriage Law and the Child Protection Law. Psychologically, an active and communicative father plays a crucial role in fostering a sense of security, self-confidence, and emotional resilience in children. The integration of these two dimensions highlights that a father's presence holds strategic importance for family balance and the development of morally grounded future generations. Therefore, strengthening the father's role through family policies and parenting education that emphasize cooperation between both parents is essential to building a harmonious and empowered family.